Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702375
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Visual Feedforward for Target Expansion Techniques

Abstract: Target expansion techniques facilitate the pointing task by enlarging the effective sizes of targets. When the target expansion is applied to both the motor and visual spaces, the visual feedforward mechanism is key: Indeed it provides a visual aid to the user on the effective expanded targets prior to the execution or completion of the pointing task, enabling the user to take full advantage of the target expansion technique. Focusing on feedforward mechanisms, we introduce a design space that allows us to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 19 publications
2
40
1
10
Order By: Relevance
“…Displaying a bubble was the typical visual feedforward for such a technique. However Guillon et al's showed that, in a 2D context, highlighting the nearest target is more efficient, and produces less visual clutter [16,17]. We extended their results to 3D interaction, with similar conclusions.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Displaying a bubble was the typical visual feedforward for such a technique. However Guillon et al's showed that, in a 2D context, highlighting the nearest target is more efficient, and produces less visual clutter [16,17]. We extended their results to 3D interaction, with similar conclusions.…”
Section: Resultssupporting
confidence: 74%
“…The main drawback remains the visual feedback introduced by the bubble constantly changing its radius. Guillon et al have evaluated the impact of several visual feedbacks on performance for the Bubble Cursor and found that a simple highlight of the closest target is efficient [17].…”
Section: Pointing Facilitation Techniquesmentioning
confidence: 99%
See 3 more Smart Citations